2007
DOI: 10.1002/qua.21477
|View full text |Cite
|
Sign up to set email alerts
|

Density functional computations of alkynylation of ethanimine catalyzed by chiral zinc(II)‐complexes

Abstract: ABSTRACT:The alkynylation of ethanimine catalyzed by chiral zinc(II)-complexes was studied by means of the density functional theory (DFT). All the intermediates and transition states were optimized completely at the B3LYP/6-31G(d,p) level. Calculation results confirm that the alkynylation of ethanimine is exothermic and the total released energy is about Ϫ13 kJ/mol. The formation of the catalyst-alkynyl complexes M4 is the rate-determining step for this alkynylation, and the formation of the catalyst-amine co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Carreira's group has examined many researches on the enantioselective addition of terminal alkynes to aldehydes or imines and suggested a single-zinc model of reaction mechanism [2,[8][9][10][11][12][13][14][15]. The reaction mechanism of zinccatalyzed alkynylation of aldehydes or ethanimine has been investigated by our group at B3LYP/6-31G(d,p) level [26,27]. However, theoretical data available for the mechanism of the addition of terminal alkynes to nitrones are rather limited, and these quantum chemical studies on the mechanism of single-zinc-catalyzed alkynylation of nitrones are hardly reported.…”
Section: Introductionmentioning
confidence: 98%
“…Carreira's group has examined many researches on the enantioselective addition of terminal alkynes to aldehydes or imines and suggested a single-zinc model of reaction mechanism [2,[8][9][10][11][12][13][14][15]. The reaction mechanism of zinccatalyzed alkynylation of aldehydes or ethanimine has been investigated by our group at B3LYP/6-31G(d,p) level [26,27]. However, theoretical data available for the mechanism of the addition of terminal alkynes to nitrones are rather limited, and these quantum chemical studies on the mechanism of single-zinc-catalyzed alkynylation of nitrones are hardly reported.…”
Section: Introductionmentioning
confidence: 98%